Teacher-researcher: conceptions and practices of master teachers working in primary education - Rita Buzzi Rausch (Revista Diálogo Educacional, 2012)
Although teacher education seeks to form a teacher-research and the research being wellness recognized as a key activity, excellent use and meaning has generated controversy. in this sense, we have investigated: which are the conceptions and practices of research master degree teachers who work in teaching at elementary schools? The objective was to identify the concepts and practices in search of master teachers. This qualitative study that we conducted in semi structured interviews with eight master professors. For the design of the teacher-researcher we have identified three aspects: a) the professional who remains up-to-dated, b) That the professional prioritizes the research over teaching, c) the professional who investigates his / her teaching practice. However, we have not noticed the correct understanding of research as a systematic process, in order to the science related to teaching. Most teachers demonstrated interest in and ability conducting research in the school, however, they have expressed impossibilities due to limiting factors related to the physical structure, lack of time, low salary and poor support from the school managers. They have noticed that the master's contributed in his /her training as a teacher-researcher. This study allowed us to analyze the educational literature which gives an emphasis on the need to train the teacher-researcher. However, it is not often discussed the history of the teachers' training, working conditions, career, the financial resources and the infrastructure also necessary for the teacher to be able to conduct research in the schools.